mTOR Promotes Tissue Factor Expression and Activity in EGFR-Mutant Cancer - Cong, Ying; Li, Qingrou; Zhang, Xuesai; Chen, Yaqing; Yu, Ker (Frontiers in Oncology, 2020)
mTOR signaling pathway mediates the function of oncogenic receptor tyrosine kinases (RTKs). We aimed to elucidate new role of mTOR in EGFR-mutant (EGFR-mut) non-small cell lung cancer (NSCLC) and glioblastoma (GBM) with a focus on tumor microenvironment. Here, we report a novel regulatory link between mTOR complexes (mTORCs) and tissue factor (TF), an initiator of tumor-derived thrombosis. TF is elevated in EGFR-mut NSCLC/GBM cell lines and tumor tissue of patients with poor prognosis. Application of mTORC1/2 inhibitors (AZD8055, WYE-125132, MTI-31 and rapamycin) or genetic mTORC-depletion all reduced TF expression, which were differentially mediated depending on cellular context. In U87MG and HCC827 cells, mTORC1 exerted a dominant role via promoting TF mRNA transcription. EGFR-TKI-resistant H1975 and PC9 cells, it was mTORC2 that played a major role through repressing of lysosomal-targeted TF protein degradation. Inhibition of TF expression and activity was demonstrated in AZD8055- or MTI-31-treated H1975 and U87MG xenograft tumors in mice while a TF-targeted antibody antagonized TF activity. Both the mTOR- and TF-targeted therapy induced a multifaceted remodeling of tumor microenvironment reflecting not only a diminished hypercoagulopathy state (fibrin level) but also a reduced stromal fibrosis (collagen distribution), compromised vessel density and/or maturity (CD31 and/or -SMA) as well as a substantially decreased infiltration of immune-suppressive M2-type tumor-associated macrophages (CD206/F4/80 ratio). Thus, our results have identified TF as a functional biomarker of mTOR in EGFR-mut cancer cells. Downregulation of mTOR-TF axis activity may contribute to the therapeutic mechanism of mTORC1/2- and TF-targeted agents in EGFR-mut advanced NSCLC and GBM.